2022
DOI: 10.3390/ani12050614
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Role of Healthy and Sick Equids in the COVID-19 Pandemic through Serological and Molecular Testing

Abstract: More and more studies are reporting on the natural transmission of SARS-CoV-2 between humans with COVID-19 and their companion animals (dogs and cats). While horses are apparently susceptible to SARS-CoV-2 infection based on the homology between the human and the equine ACE-2 receptor, no clinical or subclinical infection has yet been reported in the equine species. To investigate the possible clinical role of SARS-CoV-2 in equids, nasal secretions from 667 horses with acute onset of fever and respiratory sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 32 publications
2
31
1
Order By: Relevance
“…A recent serological survey from China, did not find antibodies specific to SARS-CoV-2 from 18 healthy horses [ 12 ]. This was in sharp contrast to a study evaluating silent transmission of SARS-CoV-2 between racetrack workers with asymptomatic COVID-19 and racing Thoroughbred horses [ 10 ]. The latter study showed that 5.9% of healthy racehorses had detectable antibodies to SARS-CoV-2, suggesting possible spillover from COVID-19 humans to horses.…”
Section: Introductioncontrasting
confidence: 67%
See 4 more Smart Citations
“…A recent serological survey from China, did not find antibodies specific to SARS-CoV-2 from 18 healthy horses [ 12 ]. This was in sharp contrast to a study evaluating silent transmission of SARS-CoV-2 between racetrack workers with asymptomatic COVID-19 and racing Thoroughbred horses [ 10 ]. The latter study showed that 5.9% of healthy racehorses had detectable antibodies to SARS-CoV-2, suggesting possible spillover from COVID-19 humans to horses.…”
Section: Introductioncontrasting
confidence: 67%
“…Apparently, horses follow the same pattern after infection with SARS-CoV-2. This observation is also supported by the inability to detect SARS-CoV-2 by RT-qPCR in 667 horses with fever and respiratory signs [ 10 ]. The lack of SARS-CoV-2 detection via RT-qPCR in the horse that seroconverted likely related to the short shedding period and the weekly sample collection interval.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations